P89 Osteopontin promotes lymphocyte recruitment in steatohepatitis. (6th September 2011) - Liaskou, E; Claridge, L C; Shah, H; Oo, Y; Shaw, J; Mi, Z; Kuo, P C; Canbay, A; Diehl, A M; Adams, D H; Syn, Wing-Kin
Abstract : Introduction: Steatohepatitis is the critical step in the progression to fibrosis, and is characterised by increased inflammatory cell recruitment from the circulation. The cytokine Osteopontin (OPN) is intricately involved in cell-recruitment and tissue-repair, and we reported that OPN is significantly upregulated during non-alcoholic steatohepatitis (NASH). Aim: Thus, we hypothesised that OPN promotes steatohepatitis by supporting leucocyte migration across hepatic sinusoidal endothelium. Method: Wild-type mice were fed chow or methionine-choline deficient (MCD) diet to induce NASH. After 4 weeks, mice were sacrificed; severity of disease assessed by serum aminotransferase (AST), hepatic OPN quantified by QRTPCR and immunohistochemistry, serum OPN measured by ELISA. In separate experiments, MCD-fed mice were treated with anti-OPN or IgG, and flow cytometry used to quantify numbers of liver infiltrating lymphocytes (LIL). Primary human hepatic sinusoidal endothelial cells (HSEC) were stimulated with recombinant (r) OPN (0–1000 ng/ml), and expression of adhesion molecules (ICAM-1, VCAM-1, CD31) quantified by western blot. To assess lymphocyte transendothelial migration, lymphocytes were perfused over rOPN- or vehicle-treated-HSEC, with or without TNFa (20 ng/ml) + IFNa (100 ng/ml). In separate experiments, TNFa+IFNa stimulated-HSEC were treated with sham or OPN-aptamers and total lymphocyte adhesion recorded. Human livers with NASH were immunostained for OPN, and FACS used to quantify LIL isolated from control or NASH-cirrhotic patients. Results: In mice, diet-induced NASH upregulated expression of hepatic OPN by threefold (p<0.05), serum OPN by twofold (p<0.05), and increased intrahepatic CD4 by 2.2-fold, CD8 by 4.5-fold, and NKT cells by 3.2-fold (p<0.05). MCD-fed mice treated with anti-OPN accumulated fewer CD3, CD4, CD8 and NKT cells (p<0.05), and exhibited attenuated injury (ALT: threefold reduction; p<0.02). rOPN induced expression of ICAM-1, VCAM-1 and CD31 on human HSEC, enhanced lymphocyte recruitment under conditions of flow (41%), and amplified recruitment capacity of TNFα+IFNγ stimulated HSEC (23%), while OPN neutralisation with RNA-aptamers reduced lymphocyte recruitment by 50% (all p<0.05). In humans, expression of OPN was significantly upregulated in NASH; livers from NASH-cirrhosis harboured twofold more CD4 and threefold more CD8 and NKT cells (p<0.05) than normal. Conclusion: OPN is upregulated during steatohepatitis in mice and humans, and promotes lymphocyte recruitment across HSEC. Neutralisation of OPN significantly reduces lymphocyte recruitment and liver injury. Our results suggest that OPN is a promising anti-inflammatory target in steatohepatitis.